Identifying and treating resistant hypertension in PRECISION: A randomized long‐term clinical trial with aprocitentan. Issue 7 (9th June 2022) - Danaietash, Parisa; Verweij, Pierre; Wang, Ji‐Guang; Dresser, George; Kantola, Ilkka; Lawrence, Mary Katherine; Narkiewicz, Krzysztof; Schlaich, Markus; Bellet, Marc; ,
Abstract: The design and baseline data of the PRECISION study, which evaluates the effect of the dual endothelin receptor antagonist aprocitentan on blood pressure (BP) in patients with resistant hypertension (RHT) are presented. The study is a blinded, randomized, parallel‐group Phase 3 study and its three‐part design assesses the short‐term and sustained long‐term effects of aprocitentan on BP. Results are expected in 2022. Patients with uncontrolled BP (measured as unattended automated office BP) despite the use of three or more antihypertensive medications for at least 1 year were screened. They were switched to a single‐tablet triple fixed combination antihypertensive therapy for at least 4 weeks before entering a single‐blind placebo run‐in period. The 4‐week placebo run‐in period further excluded placebo responders. The randomization period consisted of three sequential parts: (1) a 4‐week double‐blind part with aprocitentan 12.5 mg, 25 mg, or placebo (1:1:1 ratio); (2) a 32‐week single‐blind part with aprocitentan 25 mg; and (3) a 12‐week randomized withdrawal part with aprocitentan 25 mg or placebo (1:1 ratio). The purpose was to demonstrate the BP lowering effect of aprocitentan in RHT (Part 1) and the persistence of this effect (Parts 2 and 3). Out of 1965 screened patients, 730 were randomized resulting in an overall inclusion failure rate of 62.8%. The most common reason for exclusion (44.4% of all screened patients) was failure to meet the BP inclusion criteria. These results underline the high proportion of pseudoresistant hypertension among patients referred for RHT.